An evaluation of space planning towards habitable house design for low-income group in Mukalla and Shibam, Yemen - Baeissa, Anwar Ahmed Abdullah (2009)
The aim of this research is to evaluate the house design and its habitable the level of satisfaction of the low-income group in Mukalla and Shibam, Yemen The study focuses on the house design of the low-income group of Modern Mukalla, and uses the traditional house design in Shibam as the reference model because of its UNESCO's recognition listed under World Heritage Site. The study commences with the definitions of house, house design and habitability. The study finds that space planning and function, interior elements house-unit, interior house comfort level, interior house servtces, and indoor socio-cultural actives are important categories for definition of the house design and its habitability. It proceeds to provide qualitative and quantitative analyses of the data of these five categories as the check-list factors. A comparison of the responses under these five categories is made for Mukalla and Shibam. The outcome of the above steps is then subjected to a further analysis using triangulation method. The study finds that the respondents who live at modern houses are slightly satisfied with their house design in Modern Mukalla. It also observes that the house design in Shibam can serve as reference model of habitable house design for Hadhramout region, Yemen. The study finally provides several useful guidelines of habitable house design for the low-income group in Hadhramout region, Yemen.